Methods of Applying Employability Skills to Students with Special Education Needs in SMPKV Shah Alam - Nur Balqis Hisham; Azmanirah Ab Rahman; Anizam Mohamed Yusof (Online Journal for TVET Practitioners, 2024)
This qualitative case study explores the methods of applying employability skills to students with special education needs at SMPKV Shah Alam. The study aims to understand the perspectives and experiences of teachers in implementing employability skills for MBPK. The research findings highlight using cooperative learning, democratic classrooms, and motivational strategies to equip MBPK with the necessary skills for future employment. The study emphasizes the importance of practical application and real-world exposure to prepare MBPK for the workforce. The findings also underscore the significance of human capital transformation and the need to focus on MBPK as essential human capital for the country’s future. The study contributes to the understanding of effective educational strategies for fostering employability skills among students with special educational needs.